2012
DOI: 10.1038/jhg.2012.75
|View full text |Cite
|
Sign up to set email alerts
|

The functional significance of microRNA-375 in human squamous cell carcinoma: aberrant expression and effects on cancer pathways

Abstract: MicroRNAs (miRNAs) are a class of small, non-coding RNA molecules consisting of 19-22 nucleotides that are involved in a variety of biological processes, including development, differentiation, apoptosis and cell proliferation. In cancer research, a growing body of evidence has indicated that miRNAs are aberrantly expressed in many types of human cancers and can function either as tumor suppressors or oncogenes. Bioinformatic predictions suggest that miRNAs regulate more than 30% of protein-coding genes. Aberr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…Thus, we found that loss of miR-375 expression enhanced cancer cell aggressiveness in ESCC. Many previous studies have shown that the expression of miR-375 is markedly decreased in several types of cancers and that miR-375 functions as an antitumor miRNA (15,24). In contrast to these antitumor activities, miR-375 is upregulated in pediatric acute myeloid leukemia (AML) and prostate cancer, suggesting that miR-375 acts as an oncogenic miRNA in these diseases (25,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we found that loss of miR-375 expression enhanced cancer cell aggressiveness in ESCC. Many previous studies have shown that the expression of miR-375 is markedly decreased in several types of cancers and that miR-375 functions as an antitumor miRNA (15,24). In contrast to these antitumor activities, miR-375 is upregulated in pediatric acute myeloid leukemia (AML) and prostate cancer, suggesting that miR-375 acts as an oncogenic miRNA in these diseases (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our previous studies demonstrated that ectopic expression of miR-375 suppressed cancer cell aggressiveness in several types of cancer cells (15). In ESCC cells, several studies have indicated that miR-375 has antitumor roles through targeting oncogenic genes (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…miR-375 was one of the most significantly downregulated microRNAs in that study. Dysregulated expression of miR-375 has also been detected in lung cancer, squamous cervical cancer, colon cancer and glioma (Bierkens et al, 2013; Chang et al, 2012; Dai et al, 2012; He et al, 2012; Isozaki et al, 2012; Kinoshita et al, 2012; Li et al, 2012b; Nohata et al, 2011; Ward et al, 2012). Interestingly, AEG-1/MTDH/LYRIC is a validated target of miR-375 (Ward et al, 2012).…”
Section: Mechanisms Of Aeg-1/mtdh/lyric-mediated Drug Resistancementioning
confidence: 99%
“…MiR‐375 has been described as downregulated in several tumor entities, such as tumors of the stomach, head and neck, esophagus, cervix, brain, colorectum and liver, in both primary tumor tissue and blood‐based fluids (reviewed in Ref. ]). It has been suggested that miR‐375 has tumor‐suppressive capabilities in several types of human squamous cell carcinomas .…”
Section: Discussionmentioning
confidence: 99%